Industrial Chain, Supply Chain and Value Chain in the Energy Industry: Opportunities and Challenges (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Amidst geopolitical conflicts and energy trade wars challenging the global energy market, this Special Issue addresses critical aspects of the energy sector's transformation. It focuses on expanding and optimizing the industry, supply, and value chains through digital and innovative strategies to improve market-oriented energy distribution. Data-driven economic growth and digital technology advancements are reshaping energy governance, pushing for a shift towards renewable sources and digital solutions to overcome traditional system limitations and the "impossible triangle" of energy security, economic growth, and efficiency. This collection of 10 papers explores the opportunities and challenges in digital governance and sustainable development within the energy sector. By examining the rapid evolution of the digital economy and the urgent need for low-carbon solutions, this Special Issue contributes valuable insights into achieving a sustainable global energy transition, highlighting the importance of innovative approaches in navigating the complexities of modern energy systems.